2019
DOI: 10.1111/jpc.14342
|View full text |Cite
|
Sign up to set email alerts
|

Functional gastrointestinal disorders in children and adolescents: Knowledge, practice and attitudes of Australian paediatricians

Abstract: Aim To investigate paediatricians' understanding of, and approaches to, the diagnosis and treatment of functional abdominal pain (FAP) and irritable bowel syndrome (IBS) in children. Methods This study used an electronic survey of doctors subscribing to a popular Australian‐based paediatrics email forum. Responses about investigation and management in two clinical vignettes were correlated with respondent demographic data, practice setting, attitudes and knowledge. Results The 327 respondents were mostly femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…This is reflected by a recent survey of 289 Australian Paediatricians which disappointingly reported that only 2.1% would consider referral for hypnotherapy for a child or adolescent with IBS. 34 Interestingly, the attitudes towards hypnotherapy referrals did not differ between those who believed there ‘is clear evidence for effective treatments for IBS’ and those ‘who believed there is no clear evidence for effective IBS treatments’. 34 Potential reasons for not considering GFH as a treatment for IBS, prior to our current study, may be due to the lack of previously published real-world clinical data.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is reflected by a recent survey of 289 Australian Paediatricians which disappointingly reported that only 2.1% would consider referral for hypnotherapy for a child or adolescent with IBS. 34 Interestingly, the attitudes towards hypnotherapy referrals did not differ between those who believed there ‘is clear evidence for effective treatments for IBS’ and those ‘who believed there is no clear evidence for effective IBS treatments’. 34 Potential reasons for not considering GFH as a treatment for IBS, prior to our current study, may be due to the lack of previously published real-world clinical data.…”
Section: Discussionmentioning
confidence: 92%
“… 34 Interestingly, the attitudes towards hypnotherapy referrals did not differ between those who believed there ‘is clear evidence for effective treatments for IBS’ and those ‘who believed there is no clear evidence for effective IBS treatments’. 34 Potential reasons for not considering GFH as a treatment for IBS, prior to our current study, may be due to the lack of previously published real-world clinical data. Other potential reasons may be a lack of access and availability of appropriately trained therapists, lack of knowledge and the need for further education.…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, 327 paediatricians commented on two clinical vignettes concerning functional abdominal pain and irritable bowel syndrome. 15 These authors concluded that there was a lack of awareness of evidence-based therapies for these two FGIDs in the population studied, and only 37% of respondents were aware of the international diagnostic criteria relating to FGIDs. 16 Clearly, there are many different health-care professionals that come into regular contact with infants with FGIDs and their families, and treatment and care are not consistent between HCPs or, in many cases, with recommended treatment algorithms.…”
Section: What This Paper Addsmentioning
confidence: 96%
“…Finally, a recent study investigated knowledge, practice and attitudes of Australian paediatricians in relation to FGIDs in children and adolescents. Specifically, 327 paediatricians commented on two clinical vignettes concerning functional abdominal pain and irritable bowel syndrome 15. These authors concluded that there was a lack of awareness of evidence‐based therapies for these two FGIDs in the population studied, and only 37% of respondents were aware of the international diagnostic criteria relating to FGIDs 16…”
mentioning
confidence: 99%
“…Diagnosis and management of FGIDs are challenging for paediatric clinicians, where parental attitudes and responses to their child's pain has a significant impact on outcomes. Clinicians may be reluctant to make a diagnosis of an FGID, fearing they have missed serious underlying organic disease, leading to unnecessary and costly investigations 19 or referrals that may heighten the child and parent's concern that there is a serious organic condition present. Children with FGIDs may have seen many other health-care practitioners and have school non-attendance, and there is often considerable distress within the family, who are keen for the elusive diagnosis and rapidly effective therapy.…”
Section: Assessment and Management Of Pain-predominant Fgidsmentioning
confidence: 99%